A preparação de imigrantes haitianos para a produção da redação do Enem - Desirée de Almeida Oliveira (2019)
This dissertation investigates Haitian immigrants’ preparation for the Enem (Exame Nacional do Ensino Médio) essay writing test in the context of the classes of the Pró-Imigrantes project, in Belo Horizonte (MG). For this purpose, we engage in action-research oriented toward the development of students’ language capacities. The following specific objectives unfold: 1) analyze the mobilization of significance capacities in order to strengthen arguments in essays; 2) analyze the mobilization of linguistic-discursive capacities related to connection in order to promote progression in essays; 3) analyze possible specificities to be considered during the implementation of a didactic sequence in the focused context. Based on the theoretical framework of Sociodiscursive Interactionism (BRONCKART, 1999) and in dialogue with the literature in the field of Portuguese as a Welcoming Language (e.g. AMADO, 2013, SÃO BERNARDO, 2016; LOPEZ; DINIZ, 2018), it is conducted an interpretive analysis of the generated records: nine students’ essays, transcripts of the audio-recorded lessons, and students’ answers to questionnaire and interview. Analysis results reveal that students developed their significance capacities (CRISTOVÃO; STUTZ, 2011) in the course of the didactic sequence implementation, considerably mobilizing them in order to strengthen arguments in essays. Also, it was verified the development of linguistic-discursive capacities (DOLZ; PASQUIER; BRONCKART, 1993) related to connection by means of the mobilization of a greater number and variety of logic-argumentative organizers in essays. Finally, we observe the need of an intercultural approach as one of the specificities for a didactic sequence implementation in the focused context. Besides contributing to a welcoming classroom environment and appreciation of students’ origin and identity, the intercultural approach helped emerge Haitian cultural aspects that could be mobilized for the purpose of argumentation in essays, as well as revealed cultural differences between Haiti and Brazil that could make writing about certain topics more difficult. An unfolding aspect of this research is its potential social impact when it comes to discussing, in light of the conducted analysis, possible implications for the access of refugees and other vulnerable immigrants to higher education in Brazil. In this regard, we question the adequacy of the Enem, in particular its essay writing test, as selective criterion for this population.